2016
DOI: 10.21301/eap.v11i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Permanent museum collections from alternative classrooms to tourist attractions: Comparative analysis of visits to National Museum of Valjevo's collections in periods from 1951 to 1961 and from 2001 to 2011

Abstract: Apstrakt: Svrha ovog rada je da se sagledaju razlike u strukturi posete stalnim muzejskim postavkama u različitim periodima i da se ukaže na zadatke koje muzeji imaju u savremenom trenutku. Posle uvodnih razmatranja, gde je prezentovana problematika vezana za pitanja vrste muzejske publike i vrste muzejskih programa, centralni deo rada predstavlja prezentacija rezultata analize broja i strukture posetilaca stalnih muzejskih postavki Narodnog muzeja Valjevo u dva perioda koja deli poluvekovno razdoblje: od 1951… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the first task, (examination of types of online learning resources), it was determined that out of the total number of museums in Serbia that were initially included in the survey, 90.48% have websites. This result is significant, especially if we consider data from previous research (Krivošejev, 2013), which found that 57.50% of nominally regional museums in Serbia had their own websites, that the average website had only the most basic information, while virtual solutions were almost completely absent. Given the intense social and technological changes, it is logical that our research, conducted eight years later, yields a completely different picture.…”
Section: Discussionmentioning
confidence: 85%
“…In the first task, (examination of types of online learning resources), it was determined that out of the total number of museums in Serbia that were initially included in the survey, 90.48% have websites. This result is significant, especially if we consider data from previous research (Krivošejev, 2013), which found that 57.50% of nominally regional museums in Serbia had their own websites, that the average website had only the most basic information, while virtual solutions were almost completely absent. Given the intense social and technological changes, it is logical that our research, conducted eight years later, yields a completely different picture.…”
Section: Discussionmentioning
confidence: 85%
“…With the possibility of permutations, from the base to the top, the stairs -segments of the audience's pyramid would consist of: city population, tourists, schoolchildren and students, elderly people, special social groups, emigrant groups, people with disabilities, business elites, media professionals, professionals in the field of culture and professional museum activists (Molar, 2000;Dragićević-Šešić & Dragojević 2005;Krivošejev & Bjeljac 2016).…”
Section: Museums and Tourismmentioning
confidence: 99%
“…When it comes to permanent museum exhibitions, besides their significance for an educational mission directed towards the domicile population, these exhibitions can have key importance for tourists to have a better understanding of the nature, history and population of the receptive area, adding value to the attractions of the destination and creating motivation for a tourist visit. (Krivošejev, Bjeljac, 2016). According to their content, special programs may target both locals (lectures, tribunes and presentations to debate issues important for the community) and tourists (concerts, plays, etc.…”
Section: Museums and Tourismmentioning
confidence: 99%
See 1 more Smart Citation